Back to Work: Labor Reintegration Processes in Subjects with Drug Addiction in Rehabilitation - Navarro Becerra, Ana Araceli (2024)
The objective of this article is to give an account of the labor reintegration process in subjects in condition of drug addiction during their rehabilitation. Using a qualitative methodology, in-depth interviews were conducted with ten people in addiction in rehabilitation. Those who were interviewed have more than 15 years of sobriety and are part of a self-help group that implements the 12-step program of Alcoholics Anonymous in Guadalajara, Jalisco, Mexico. Among the results, it stands out that labor reintegration is a process that involves several phases, one of them is the period of service where the subject is prepared in the practice of punctuality, responsibility, commitment, and respect, as well as in emotional management for the performance of paid work. The decision of when, where and what activity to carry out falls, in principle, on the sponsor and the employer, since it depends on the subject’s progress in their rehabilitation, the management of their emotions and the establishment of non-conflictive interpersonal relationships. To assign work activities, support networks made up of members of the self-help group are used, since the subjects must be monitored to avoid emotional and consumption relapses.